The Development of Sports Management Research in Indonesia in the Early Twenty-First Century: A Bibliometric Analysis - Davi Sofyan (Universitas Majalengka, 2022)
The purpose of this research is to provide a comprehensive elaboration by describing the descriptive parameters of the publication and extracting the author's keywords in the field of sports management. This study includes a primer for researchers to better understand advances in scientific publications related to exercise management. A thorough examination of the 220 documents found in the Scopus database was carried out from 2003 to 2022 (as of March, 7 2022). According to the findings, the number of publications fluctuated, with the most publications occurring between 2018 and 2020, with a total of 111 documents. Furthermore, with a total of 26 documents, the Journal of Physics Conference Series is the title of the most productive scientific source. Overall, this topic's research is evolving, with new methods and directions being established. As a result, a thorough examination of sports management in a variety of research areas can help researchers and practitioners advance prospective knowledge in these fields.